The biological activity of fermented milk produced by Lactobacillus casei ATCC 393 during cold storage. (April 2019) - Abdel-Hamid, Mahmoud; Romeih, Ehab; Gamba, Raúl Ricardo; Nagai, Emiko; Suzuki, Takuya; Koyanagi, Takashi; Enomoto, Toshiki
Abstract: Lactobacillus casei ATCC 393 is an important probiotic strain widely known in dairy technology. However, its capability to produce bioactive peptides from milk proteins has not been studied. The viability of the Lb . casei ATCC 393 strain and some physicochemical properties in fermented milk throughout storage for 21 days at 4 °C was evaluated; biological activity, i.e., antioxidant, angiotensin converting enzyme inhibitory and anticancer activities of water soluble extract and its filtrate (< 2 kDa; F1) were determined. Lb . casei counts remained over 9 log cfu g −1 during the storage period in fermented milk. These bioactivities were increased significantly ( P < 0.01) during storage. F1 of fermented milk after three weeks of storage showed the highest bioactivity impact. De novo sequencing assay for peptide identification was applied to the mass spectrum of F1. The promising capability of Lb . casei ATCC 393 to release bioactive peptides from milk proteins was demonstrated.